2018
DOI: 10.1182/bloodadvances.2017014720
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of bone marrow abnormalities in the appendicular skeleton of patients with multiple myeloma

Abstract: Key Points• Bone marrow abnormalities were detected in the AS of 196 consecutive symptomatic patients with MM.• Medullary abnormalities in the AS were associated with a poor prognosis, independent of other clinical parameters.We aimed to determine the clinical and prognostic significance of medullary abnormalities detected by low-dose whole-body multidetector computed tomography ( 1.12-3.31; P 5 .018) were independent predictors of progression-free survival. Age and focal (HR, 2.51; 95% CI, 1.14-5.56; P 5 .023… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Interestingly, the presence of FL in the inferior limbs at baseline was also associated with a shorter PFS ( Table 2 ). This is in accordance with a study that found that an appendicular skeleton involvement on CT had a pejorative prognostic value [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the presence of FL in the inferior limbs at baseline was also associated with a shorter PFS ( Table 2 ). This is in accordance with a study that found that an appendicular skeleton involvement on CT had a pejorative prognostic value [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Bone marrow changes are traditionally mostly investigated and reported by magnetic resonance imaging techniques (see below), but nodular or diffuse infiltration of long bones can also be detected by WBLDCT and has been reported to have prognostic significance. Identified focal and diffuse pattern in the appendicular bone marrow by WCLDCT is associated with a shorter PFS and OS [33].…”
Section: From Conventional Skeletal Survey To Whole-body Ctmentioning
confidence: 90%
“…However, when applying the scheme of initially performing spinal/spinal plus pelvic MRI and extending the protocol in case of finding exactly one FL, still 44%/20% of patients would remain underdiagnosed according to our results, which points out that wb-MRI clearly remains the gold standard and should be performed if available. Additionally, when wb-MRI is not available but wb-CT is performed to exclude osteolysis at initial diagnosis, the CT does have some ability to detect focal bone marrow infiltrates in the appendicular skeleton [ 22 ], however the sensitivity of CT compared to MRI for these lesions is currently unclear, and their prognostic implication in SMM patients needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%